Purification and Characterization of ?-N-Acetylgalactosaminidase from Hilsha ilisha - Rashid, M. H.; Alam, A. H. M. K.; Uddin, J.; Karim, N.; Sadik, M. G. (Journal of Scientific Research, 2017)
The objective of this study was to purify and characterize the alpha-N-acetylgalactosaminidase (?-GalNAcase) from hilsha fish, Hilsha ilisha. Digestive organ of hilsha fish was found to contain a large amount of ?-GalNAcase in compared with the other tissues examined. ?-GalNAcase was purified from the crude extract of hilsha fish by ammonium sulphate precipitation, Sephadex G-200 gel filtration, and SP-Sephadex C-50 column chromatography. The purified enzyme gave a single band on sodium dodecylsulphate-polyacrylamide gel electrophoresis and exhibited a molecular mass of 48 kDa. The final preparation of ?-GalNAcase showed 3.02% ?-galactosidase activity. The enzyme had an optimum pH of 4.0 and was found to be quiet heat stable at 37°C. Inhibition studies with metal ions demonstrated that the enzyme was highly inhibited by silver and mercury ions. Both N-acetylgalactosamine and galactose affect the enzyme activity. Kinetic studies with the enzyme showed that the KM value for p-nitrophenyl-?-N-acetylgalactosaminide substrate was 3.31 mM and the Vmax value was 35.04 unit/mg.